Growth of UMKM in Dedap Village, Meranti District: Promotion, Location, and Product Quality - Sukron Niami; Mashuri; Muhammad Isa Selamat; Ade Suhartini; Kurniatul Fil Khoirin (MultiTech Publisher, 2024)
The aim of this research is to determine the growth of MSMEs through the factors that influence it. This research was conducted in Dedap Village, Tasik Putri Puyu District, Meranti Regency, Riau Province. The data analysis method uses a quantitative descriptive approach, data collection techniques are carried out by means of field observations, questionnaires and questionnaires, library data and documentation. The number of samples in the study was 102 people. Data analysis was carried out using the results of multiple linear regression calculations assisted by the SPSS 22 analysis tool. Based on the results of data analysis, promotion and product quality had a positive and significant influence on the growth of MSMEs, while location had no effect on MSME growth. Based on the results of interviews conducted in the field, buyers do not mind the location where the MSMEs are located, but customers prefer that the product is known and the quality provided can satisfy their needs